Bolsa Permanência na UFMS: novas configurações e velhos desafios - Felipe Vieira Gimenez; Carina Elisabeth Maciel (EccoS – Revista Científica)
This article aims to analyze the action "Bolsa Permanência UFMS" at the Federal University of Mato Grosso do Sul / UFMS, Campus Campo Grande / MS, as a strategy to favor the permanence in the perspective of the students, in the undergraduate courses. The present text is a result of research carried out in a network and dissertation product already defended, through which we seek the unveiling of the real, intrinsic in social practices and in the materialization of educational policies. The research is exploratory, bibliographical and documentary, presenting as sources reports and institutional documents of the MEC and UFMS for the period 2013, 2014 and 2015. The results indicate that the scholarship permanence linked to the student assistance policy in UFMS was a political strategy which favors, but does not guarantee the permanence of the students in the university campus through scholarships and financial aid granted.